Identifying Key Factors Affecting Customer’s Decision-Making of Internet Service Providers in Albania - BUHALJOTI, Ana (Management Dynamics in the Knowledge Economy, 2019)
The internet market in Albania is expanding and new Internet service providers have grown significantly. Improving competition in this market relies on understanding why customers choose a particular service provider. This research paper aims to investigate and understand how a range of factors impact the customers’ perceptions to choose their internet service provider. It explores the factors affecting customer’s decision by using a quantitative method via a questionnaire survey. For identifying behavioral factors, a survey was conducted face to face. The structured questionnaire assessed the users’ perceptions and opinions in choosing an internet provider. The target population consisted of individual internet users at the household level who have fixed internet access at home. This paper presents the variables that influence consumers purchase decision by reviewing key factors in the sector and identifies consumer patterns in purchasing Internet Service Provider (ISPs). The findings of the research showed that brand image is the most influential factor in the selection of ISPs. In order to gain new customers, internet providers have to take into consideration the company’s image as a critical factor to the consumer decision-making, followed by the information disposed to customers and the risk associated to the service provider. The research provided high-speed internet providers in Albania insights on how to gain new customers and enhance competitiveness